Transferring intermediate technologies to rural enterprises in developing economies: a conceptual framework*. (2nd April 2016) - Sánchez Preciado, Deycy Janeth; Claes, Björn; Theodorakopoulos, Nicholas
Abstract: This paper integrates the contributions from different branches of the technology transfer literature to identify enablers driving the transfer of intermediate or appropriate technologies to recipients in rural areas of developing economies. An in-depth analysis of the literature shows that many enablers identified in the literature focus on high technology transfers and are of limited relevance in the context of rural enterprises. Other important enablers in this specific setting are ignored or insufficiently considered. This paper proposes a framework comprising a specific set of enablers that facilitates technology transfer in rural enterprises in developing regional economies.